Measuring diffuse metabolic activity on FDG-PET/CT: new method for evaluating Langerhans cell histiocytosis activity in pulmonary parenchyma - Szturz, Petr; Řehák, Zdeněk; Koukalová, Renata; Adam, Zdeněk; Krejčí, Marta; Pour, Luděk; Zahradová, Lenka; Vaníček, Jiří; Nebeský, Tomáš; Hájek, Roman; Mayer, Jiří (Nuclear medicine and biology, 2012)
INTRODUCTION: Pulmonary Langerhans cell histiocytosis (PLCH) is a rare cause of interstitial lung disease characterized by formation of nodules in the active phase of the disease that evolve into nonactive cystic lesions later on. To evaluate PLCH activity in patients, we developed a new method for measuring diffuse metabolic activity on fluorine-18-fluorodeoxyglucose positron emission tomography/computed tomography (FDG-PET/CT) using a lung-to-liver activity ratio. MATERIAL AND METHODS: We retrospectively studied a series of 4 FDG-PET and 23 FDG-PET/CT scans from 7 patients with PLCH and analyzed a sample of 100 randomly chosen FDG-PET/CT studies free from any known lung or hepatic diseases. Maximum standardized uptake value (SUVmax) in a spherical volume (6-8 cm in diameter) in the right lung was put into relation with SUVmax in a spherical volume (9-10 cm in diameter) in the reference liver parenchyma to set up the SUVmaxPULMO/SUVmaxHEPAR index. The index values were compared to the disease course in each patient. RESULTS: In patients with PLCH, a close correlation between the index value and the disease course was found in all seven subjects, where the increasing index values indicated disease activity, while decreasing index values were observed after therapy administration. In the group of 100 healthy control subjects, we found index values lower than 0.3 in 80% and lower than 0.4 in 96% [range: 0.14-0.43; 0.24±0.07 (100)]. CONCLUSION: Measuring SUVmaxPULMO/SUVmaxHEPAR values and their time-trend monitoring represent simple, noninvasive screening tools allowing an early diagnosis and treatment response follow-up assessment in patients with PLCH.
Keywords: počítačová rentgenová tomografie; respirační funkční testy; Fluorodeoxyglucose F18; Humans; lidé středního věku; Histiocytosis, Langerhans-Cell; následné studie; Female; dospělí; fluorodeoxyglukosa F18; Lung; lidé; Respiratory Function Tests; plíce; Adult; ženské pohlaví; Male; Middle Aged; Retrospective Studies; Tomography, X-Ray Computed; histiocytóza z Langerhansových buněk; prognóza; Positron-Emission Tomography; retrospektivní studie; mužské pohlaví; radiofarmaka; pozitronová emisní tomografie; Prognosis; Follow-Up Studies; Radiopharmaceuticals